Response of garlic to integrated nutrient management practices in a sodic soil of Uttar Pradesh, India - L Sharma, S K Tewari, R C Nainwal, D Singh, R S Katiyar, (Journal of Spices and Aromatic Crops, 2015)
An investigation was carried out to study the combined effect of biofertilizers viz., phosphate solubilizing bacteria (PSB) and Trichoderma supplemented with FYM and chemical fertilizers on plant growth and bulb yield of garlic (Allium sativum) under degraded land condition. Significantly higher values of plant growth and yield parameters were obtained with the application of 100% recommended dose of NPK supplemented with FYM along with seed treatment with Trichoderma and PSB. Seed treatment with PSB was effective for all the parameters. However, PSB and Trichoderma were more effective when applied along with 100% NPK and FYM @ 20 t ha-1. It can, therefore, be concluded that for sustainable production of garlic, application of recommended dose of inorganic fertilizer (NPK) supplemented with 20 t ha-1 of FYM coupled with inoculation of PSB and Trichoderma can enhance yield and profitability of garlic.